Spectrum of Exfoliative Cytology at Birat Medical College and Teaching Hospital - Shaukin, Shilpi; Kafle, Satosh U; Singh, Mrinalini (Birat Journal of Health Sciences, 2019)
Introduction: Exfoliative cytological study of body fluids is easy, simple, rapid, cost effective and patient compliant investigation that helps in characterizing the disease into their varying subtypes. These presumptive and sometimes definitive diagnoses are in most cases the cornerstone which helps in staging and prognosis of the patientObjective: To determine the spectrum of malignant and non-malignant lesions in exfoliative cytologyMethodology: This was a quantitative retrospective cross sectional study conducted at Birat Medical College Teaching Hospital from 24th December 2014 to 24th December 2018. All the exfoliative samples received at the lab were accepted in our study.Results: Of the 300 samples received, the maximum number were those of sputum followed by pleural fluid and ascitic fluid. Peritoneal fluid, Cerebrospinal fluid, synovial fluid, fluid from suspected abscess and breast fluid were also received. Malignancy was found in 1.67% of the samples studies.Conclusion: A study of different cytomorphological features of exfoliative cytology samples will help in establishing the role of cytology as an important diagnostic tool in improving the effectiveness of diagnosis , treatment & prognosis of the patient in the medical field.